Ineffectiveness of Law N° 30490 to guarantee the Fundamental Rights of Older Adults in a Peruvian Region - Cabrera Cabrera, Xiomara; Tapia Vásquez, Lilia Marina; Pérez Nájera, Celin (Espergesia, 2023)
The need to seek alternative solutions to the situation of abandoned, unprotected, invisibility in which older people are in vulnerable conditions was the primary motivation for developing this study, the purpose of which was to analyze the ineffectiveness in the application of Law No. 30490, which protects the fundamental rights of the elderly in Peru. The research is applied descriptive; the doctrinal legal method is used, with a mixed approach and a non-experimental cross-sectional design. Magistrates, specialists in Family Law, and authorities of public entities were taken as study units, applying a questionnaire. The observation was used as a technique; documentary analysis, articles, laws, and doctrines. The family is considered to be the main responsible for the violation of the rights of the older adult and the state itself with its entities, which must fulfill the purposes of public function, prioritizing and optimizing the resources they have, following the Law of the Framework for the Modernization of State Management. The main contribution of this research is that it concludes in a proposal, type bill, that seeks to modify article 25, Law No. 30490 of Title III, Chapter I, for a new definition of Older Adult Person, to achieve the timely identification and protection of this age group.Keywords: Demographic Aging; Older Adult Person; Vulnerability; Social Victimization.